Manajemen Pembelajaran PAI sebagai Upaya Guru dalam Menciptakan Siswa Aktif di SMP IT Al-Ghazali Palangka Raya - Supriadi Supriadi (Jurnal Hadratul Madaniyah, 2017)
This study aims to determine the management of PAI learning as a teacher who helps in the process at Al-Ghazali IT Middle School and to find out the supporting factors of PAI learning in learning conducted at Al-Ghazali IT Middle School in Palangka Raya. This research is qualitative research, namely data collected in the form of words that use several data techniques which include interview techniques, documentation and documentation. Subjects in this study were PAI teachers who were one person and supported by three informants, namely the Principal, Deputy Principal and students. The results showed that the management of PAI learning as an effort of the teacher in making active students at Al-Ghazali Palangka Raya IT Middle School starting from the syllabus planning, analysis of teaching materials, and RPP was quite good seen from the strategies outlined in preparation, organizing such as learning media, manage the number of students, and manage classrooms by school parties. In terms of implementation, starting from class VII still not seen active because it focuses on the lecture method, then in class VIII the teacher is able to involve students in it because it can correlate the learning media with the learning method, while in class IX it is not in accordance with the planning he made . Meanwhile, the evaluation was carried out, the LKS, UTS, and the end of the semester tests. The key words to support PAI learning in the making active students are learning media that contain textbooks used by each student, LCD, folding chairs, wifi, teacher, and wifi for students and teachers supported by teaching methods such as lectures, discussions, question and answer and CTL.